Void-Volume-Based Stem Geometric Modeling and Branch-Knot Localization in Terrestrial Laser Scanning Data - Aravind Harikumar; Xinlian Liang; Francesca Bovolo; Lorenzo Bruzzone (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
A comprehensive 3-D structural mapping of stem is essential for an accurate 3-D crown modeling and tree parameter estimation. Terrestrial laser scanning (TLS) is an effective technology for a comprehensive collection of individual tree level data, compared to destructive and costly field measurements. The performance of 3-D stem modeling techniques is adversely affected by laser shadowing and point-density variations in TLS data. In addition, most of the state-of-the-art techniques perform stem modeling using regular geometric shapes, such as circle, ellipse, and cylinder, which cannot accurately capture the complex 3-D stem geometric shapes. This results in stem modeling errors. In this article, we propose a 3-D stem modeling approach for both single- and multiscan TLS data that: 1) does not make any prior assumption on the stem geometry and 2) is minimally affected by undesirable stem shadowing and point-density variations. The proposed approach accurately models 3-D stem and localizes branch-knots for both coniferous and deciduous trees by mapping the void volume formed within the stem due to the opaqueness of tree stem to laser. The modeling performance was evaluated on both single- and multiscan data obtained for pine, spruce, and birch species. The low estimation errors associated with the stem diameter at breast height and branch-knot location, compared to the reference methods, prove the ability of the proposed method to both accurately model 3-D stem and localize branch-knots.